The gendered division of paid and domestic work under lockdown. (21st December 2022) - Andrew, Alison; Cattan, Sarah; Costa Dias, Monica; Farquharson, Christine; Kraftman, Lucy; Krutikova, Sonya; Phimister, Angus; Sevilla, Almudena
Abstract: This paper provides novel empirical evidence on the effects of the COVID‐19 pandemic on the division of labour between parents of school‐aged children in two‐parent opposite‐gender families. In line with existing evidence, we find that mothers' paid work took a larger hit than that of fathers, and that mothers spent substantially longer doing childcare and housework than their partners. We go further to show that these gender differences cannot be explained by gender differences in the industries and occupations in which parents worked prior to the lockdown. Nor can they be explained by gender differences in earnings prior to the crisis: independently of which parent earned the most before the pandemic, it tended to be the mothers who adjusted time spent on paid and unpaid work more significantly. This is the case even in households where only one partner remained active in paid work. While we cannot fully rule out that these asymmetric responses are explained by gender differences in productivity in domestic work, our results do suggest that other factors, such as gender norms, may play an important role.